Strategi Komunikasi Polri di Media Sosial: Studi Kasus Manajemen Reputasi Oleh Divisi Hubungan Masyarakat - Ibrahim, Sayyid Malik; Golose, Petrus Reinhard; Imran, Muhammad Fadil (Prisani Cendekia Institute, 2025)
This study is motivated by the significant challenges faced by the Indonesian National Police (Polri) in the Post Truth era, where public opinion is often influenced by misinformation and hoaxes. Polri's Public Relations Division must manage public communication with quick and transparent responses, control the narrative, and ensure accurate information to build public trust. Therefore, this research aims to analyze the issues faced by Polri's Public Relations Division in managing misinformation, disinformation, and hoaxes that harm Polri's interests in the Post Truth era and to formulate strategies for the Division to maintain and improve public trust. The theories used in this study are mass communication effects theory, agenda-setting theory, confirmation bias theory, crisis communication theory, and social construction of reality theory. The research method employed is a qualitative approach with field research. The findings show that Polri's Public Relations Division faces significant challenges in the Post Truth era, such as misinformation, disinformation, and hoaxes, exacerbated by low digital literacy, dependence on social media, and the